ANALISIS KEBIJAKAN PENILAIAN PANDU (PILOT ASSESMENT) DI KANTOR KESYAHBANDARAN UTAMA (KSU) TANJUNG PERAK SURABAYA - Yuliansyah; Budi Rianto; Sudirman; Lunariana Lubis (Prodi Sosiologi Agama, 2022)
The Harbormaster of Tanjung Perak Surabaya (KSU) conducts an assessment of the personnel on duty, namely the Pilot Assessment in order to improve the quality of service for ship delaying activities and to realize safety and security in the waters of the Tanjung Perak Port, Surabaya. KSU Tanjung Perak Surabaya issued a decree number: HK.207/01/15/SYB-Tpr-18 regarding the operational system and procedures for ship scouting and towing services in the obligatory scout waters of the Tanjung Perak Port Surabaya and Port of Gresik. The purpose of this study was to analyze the implementation of the pilot assessment policy at KSU Tanjung Perak Surabaya. The theory of implementation of the Van Meter and Van Horn policies used in this study has 6 (six) variables that form the linkage between policy and performance. This study uses a qualitative method with a case study approach to collect data through interviews, observations and documentation, then the data obtained are analyzed interactively. The results obtained are the implementation of the Pilot Assessment Policy carried out by KSU Tanjung Perak Surabaya has been running optimally and in accordance with applicable regulations.